Antiferromagnetic behavior in single-wall carbon nanotubes - V. Likodimos; Glenis, S.; Guskos, N.; Lin, C.L. (Physical Review B - Condensed Matter and Materials Physics, 2007)
The electronic properties of single-wall carbon nanotubes (SWNTs) have been studied using dc magnetization and electron spin resonance (ESR). The dc magnetization displays a weak diamagnetic susceptibility of ≈ 10-7 emu/g. ESR measurements reveal a narrow resonance line of low intensity and metallic line shape. The spin susceptibility shows a major Pauli contribution at high temperatures (T>150 K) and an appreciable Curie component at lower temperatures. A marked drop of the spin susceptibility is observed at T<14 K, pointing to the opening of a spin gap at low temperatures. The underlying mechanism is discussed in terms of an electronic instability of the SWNTs or the occurrence of defect-mediated spin magnetism. © 2007 The American Physical Society.